2015
DOI: 10.1016/j.jadohealth.2014.10.275
|View full text |Cite
|
Sign up to set email alerts
|

Does It Get Better? A Longitudinal Analysis of Psychological Distress and Victimization in Lesbian, Gay, Bisexual, Transgender, and Questioning Youth

Abstract: Purpose The mental health and victimization of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) youth have garnered media attention with the “It Gets Better Project.” Despite this popular interest, there is an absence of empirical evidence evaluating a possible developmental trajectory in LGBTQ distress and the factors that might influence distress over time. Methods This study used an accelerated longitudinal design and multilevel modeling to examine a racially/ethnically diverse analytic sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
157
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(185 citation statements)
references
References 35 publications
22
157
4
2
Order By: Relevance
“…Data collection was conducted in 2013 and 2014. Further description is reported elsewhere (Birkett, Newcomb, & Mustanski, 2015; McConnell, Birkett, & Mustanski, 2016; McConnell, Birkett, & Shattell, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Data collection was conducted in 2013 and 2014. Further description is reported elsewhere (Birkett, Newcomb, & Mustanski, 2015; McConnell, Birkett, & Mustanski, 2016; McConnell, Birkett, & Shattell, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Initial evidence concerning sexual orientation disparities in depressive symptoms trajectories comes from the National Longitudinal Study of Adolescent to Adult Health. 9 -11 Using 4 waves of National Longitudinal Study of Adolescent to Adult Health data covering a 13-year period (from wave 1 in 1994-1995 to wave 4 in 2007-2009), trajectory analyses revealed that sexual orientation disparities in depressive symptoms were present as early as adolescence (grades [7][8][9][10][11][12] and persisted into early adulthood (ages 24-32 years), 10 and these disparities were more pronounced among female participants. 11 Trajectory studies using more recent samples revealed conflicting evidence.…”
mentioning
confidence: 99%
“…In a Chicago sample of sexual minority adolescents aged 16 to 20 years, depressive symptoms were found to decrease over a 3.5-year period. 12 In the Dutch Tracking Adolescents' Individual Lives Survey cohort, sexual minority status was associated with increases in depressive symptoms among younger adolescents who were longitudinally followed from age 11 to 22 years. 13 To more fully understand whether these mixed findings are due to variations in the measurement of sexual orientation, when and where the study took place, or differences in the developmental stage examined, trajectory studies of depressive symptoms using more recent population-based samples are needed.…”
mentioning
confidence: 99%
“…The YouTube-based project's goal is to inspire LGBTQ youth with positive stories by LGBTQ adults who were victimized or contemplated suicide in their youth but experienced dramatic improvement in their lives as they grew older. The project has received more than 50,000 video submissions and drawn supporters and submissions from individuals such as Barack Obama, various celebrities, and staff members of major corporations, such as Facebook and Google (Birkett, Newcomb, & Mustanski, 2014). Such projects have a potentially revolutionary effect, by both raising public awareness of bullying and discrimination against queer youth and providing desperately needed voices, stories, and role models that enable queer youth to develop and define their own identities.…”
Section: The Challenge Of New Technologiesmentioning
confidence: 99%